The Task Force for the management of arterial hypertension of the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) 2018 ESC/ESH Guidelines for the management of arterial hypertension - Article Editorial (Российский кардиологический журнал, 2018)
Text is available in electronic version doi:10.15829/1560-4071-2018-12-143-228